2019
DOI: 10.18203/2394-6040.ijcmph20193494
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immunization coverage and associated factors among children in Paravur Taluk of Ernakulam district, Kerala

Abstract: Background: Immunization is one of the most cost-effective interventions averting countless childhood deaths and protecting millions of children from disability and illness. The objective of the current study was to assess the immunization coverage and associated factors among children aged 12-23 months and 5-7 years in Paravur Taluk of Ernakulam district, Kerala.Methods: A community based cross sectional study was done. Cluster sampling method of WHO was used for evaluation of immunization coverage.300 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The slightly reduced immunization status in our study might be due to socio-economic factors. 10 This study showed that 92.3% mothers practiced immunization. Similar findings were reported by Lamiya in her study which showed that 88% mothers practiced immunization.…”
Section: Discussionmentioning
confidence: 79%
“…The slightly reduced immunization status in our study might be due to socio-economic factors. 10 This study showed that 92.3% mothers practiced immunization. Similar findings were reported by Lamiya in her study which showed that 88% mothers practiced immunization.…”
Section: Discussionmentioning
confidence: 79%